Cortical visual evoked potentials in very low birthweight premature infants. Issue 1 (1st January 2002) - Atkinson, J; Anker, S; Rae, S; Weeks, F; Braddick, O; Rennie, J
Abstract : Objectives: To compare the age of onset of the pattern orientation reversal visual evoked potential (OR-VEP) in a group of very low birthweight (VLBW) premature infants with term infants matched for postconceptual age at testing. The OR-VEP measure is used as an indicator of visual cortical functioning because of the specificity of cortical neurones in showing sensitivity to changes of slant or orientation. Design: Results are given for 24 VLBW infants, born at 24–32 weeks gestation weighing less than 1500 g, and 31 infants born at term. The steady state evoked potential to a grating pattern reversing in orientation (between 45° and 135°) at 4 reversals/second and 8 reversals/second was recorded. Results: The VLBW infants with normal neonatal ultrasound results (and normal neurological outcome at 3 years of age) showed a significant OR-VEP with a similar postnatal time course to the term infants. Four premature infants, showing appreciable abnormalities on ultrasound examination, did not show normal onset of the OR-VEP, and all had an abnormal neurological outcome. Conclusions: This result can be taken to indicate that the onset of cortical function is similar in healthy preterm infants to term infants. The visual development of the premature infants was neither accelerated nor delayed as a result of their extra visual experience. The OR-VEP can be used as a prognostic indicator of early brain development alongside other neurological measures. It may also be a very early indicator of later neurological outcome.